Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan dalam Membentuk Loyalitas Pelanggan - ARYANI, DWI; ROSINTA, FEBRINA (UI Scholars Hub, 2011)
The aim of the research is to analyze how the service quality can affect customer’s satisfaction in shaping costumer’s loyalty. The research is quantitative and uses non-probability purposive sampling technique. The instrument of the research uses questionnaires which were analyzed with Structural Equation Modeling. The result of the research shows that the five dimensions, i.e. physical evidence, empathy, reliability, quickness, and guaranty positively affect the service quality. The other results show that customer’s satisfaction is a preceding factor of customer’s loyalty. The direct effect of service quality on customer’s loyalty does not sustain the research, since the researcher did not find any significant direct relation between service quality and customer’s loyalty.